Leading the introduction and development of lesson and learning study in an English Secondary Academy. Issue 1 (3rd January 2017) - Austin, Lucy
Abstract : Purpose: At "The Academy" the author has undertaken five lesson study (LS) cycles to date and the outcomes of these are discussed with consideration to the local context, the culture and the wider context which have surrounded the six-year period of implementation. The emphasis here is not to present pedagogical outcomes of the LS but to present the leadership challenges they have presented and how these have been overcome. The paper aims to discuss these issues. Design/methodology/approach: This paper is presented as a case study and uses the author's personal reflections on the approaches used thus far to implement LS within the specific context. The author also uses a review of data concerning continuous professional development (CPD) within "The Academy" along with interviews with some of the teachers who have been involved. Findings: LS is an emerging form of CPD in the UK and even when implemented does not yield a wealth of quantitative data which can be used to prove the impact it can have; consequently implementing LS can be perceived as a risk within the profession. The author explores whether the "impact" which is emerging is everything the author expected it to be, or indeed everything it needs to be. The author discovers the culture we are working in, with increasing pressures on time and increased dependence on quantitative data, requires leaders to manage the associated perceived risks in order to successfully implement LS. Originality/value: This paper is intended to provide useful insights for senior leaders and leaders of LS who are in the process of implementing LS within their own contexts.